Overwhelming Streptococcus pyogenes sepsis in an elderly patient with septic arthritis. Issue 3 (May 2018) - Chadha, Aarti; Jamal, Wafaa; Aziz, Abdul R.A.; Rotimi, Vincent O.
Abstract: Introduction: The signs of Streptococcus pyogenes, group A streptococci (GAS) bacteremia are non-specific and patients can have wide presentations ranging from flu-like symptoms to life-threatening toxic-shock syndrome in just a few hours. Case presentation: We report a case of fulminant S. pyogenes sepsis in an elderly woman with septic arthritis and remarkable past medical history/risk factors. She was febrile, hypotensive and had a swollen and tender right knee. Multiple blood cultures and the synovial fluid culture yielded S. pyogenes . Despite adequate antimicrobial therapy with penicillin and clindamycin the patient succumbed to her infection within 4 days of presentation in our hospital. Conclusion: GAS remains penicillin sensitive most of the time but prompt appropriate antibiotic therapy is very crucial to survival.